Penentuan Critical Control Point (Ccp) Pada Proses Pengalengan Ikan Lemuru (Sardinella,Sp) Di PT Sarana Tani Pratama, Bali - Hasriani Hasriani; Muhammad Ridwan; Andi Rusdi Walinono (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
Critical Control Point (CCP) a point, stage, or procedures where the danger that related with food can be prevented, eliminated or reduced to the point that can be accepted (allowed or secure point). The purpose of this research is to know the level of the determination of Critical Control Point (CCP) on the process of fish canning sardinella,SP and know the critical control point on the process of fish canning sardinella,SP. This study uses qualitative data obtained from interviews, surveys, observations and documentation using data reduction analysis, data presentation, verification and decisionmaking trees. The results of this study show that the Application of Critical Control Point (CCP) in the Lemuru Fish Canning Process (Sardinella Lemuru) at PT Sarana Tani Pratama has been effective even though there are several elements that need more attention so that its application can be in accordance with the guidelines for good food production methods. Critical control points (CCP) in the process of canning lemuru fish (Sardinella, sp), are as follows: 1) Acceptance of raw materials (frozen & fresh), 2) Closure of cans (seammer), 3) Sterelization / Retort.